Pengaruh Komunikasi Interpersonal Guru Dalam Meningkatkan Kedisiplinan Siswa - Suchyadi, Yudhie; Martha, Layung Paramesti (Universitas Pakuan, 2023)
THE INFLUENCE OF TEACHERS' INTERPERSONAL COMMUNICATION IN IMPROVING STUDENT DISCIPLINETeachers have an important role in determining the success in influencing their students to improve discipline, closely related to the character inherent in the teacher himself. The purpose of this study is to determine how the influence of teacher interpersonal communication on the formation of student discipline. This study is a qualitative study, which uses a qualitative descriptive approach. The subjects in this study were 5 teachers and 60 students. Data collection was carried out by interviews, questionnaires, observations, and documentation. The results of the study indicate that communication between teachers and students has not been running optimally in improving discipline. The factor behind this problem is the level of understanding between teachers and students regarding the importance of communication in the teaching and learning process is still low. So a teacher must continue to be able to improve his ability to convey his learning messages to students, without forgetting to involve all existing components, so that an understanding is built between teachers and students in order to achieve the goals of the teaching and learning process and pay attention to several inhibiting factors of the communication, namely, teachers as communicators, subject matter, media, students, effects, environment, feedback, and methods. Interpersonal communication between teachers and students can also change students' attitudes to be disciplined and can develop a disciplined attitude. This shows that interpersonal communication between teachers and students has a positive effect on student discipline.